BODY WEIGHT CHANGES, MORPHOMFXRY AND ATTACHMENT OF PUBERTY IN CAPTIVE BRED GRASSCUTTERS (17zryotzomys swinderarianus Ternmirick) - ONADEKO, S. A. (Nigerian Journal of Animal Science, 2023)
A systematic investigation was conducted to determine attainment of puberty, morphmetric and body weight changes in grasscutters reared in captivity mean birth weight of captive-bred grasscutters was 117.70 + 34.00g. (N=36). Males (X+118=28.70g, N=16) were significantly (P<0.01) heavier than the females (X==100.90+-27.56g, N=20). Males consistently showed higher rates of live weight gain than the females. At 36& week, a male grasscutter had attained 1.6kg rive weight while a female was 950g Mean age at puberty was estimated 252.50 day for male and 214.67days for the female. With the exception of the shoulder height at birth, body linear measurements were longer in the male than the female and consistently increased throughout the study period. The relationship between each morphometric index and body weight was significantly (P<0.01) linear and strongest (r=0.98) between body weight and heart girth.